Application of the institute of income redistribution in the form of social transfers in EU countries - Irena Antošová; Jana Stávková (DANUBE: Law, Economics and Social Issues Review, 2019)
The reduction in the number of households living at risk of poverty is a common objective of EU countries but the social policy of each member state is different. This paper provides an overview of components of social transfers and their share in total household incomes in EU countries. The aim of the paper is to assess the effectiveness of the social systems of each on the basis of the number of households at risk of poverty determined before and after the payment of social benefits. Four segments of EU countries were identified in cluster analysis according to their approach to social transfer settings using primary data from EU-SILC survey. The combination of high share of social benefits and low share of old age pensions proves to be better in the fight against poverty. The relationship between an economic performance and a functioning social policy system appears in EU countries.
Keywords: 330; Social Transfer; Income Inequality; Poverty; Social Benefits; Old Age Pension